2023
DOI: 10.1007/s40263-023-01013-8
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Event Profiles of Antiseizure Medications and the Impact of Coadministration on Drug Tolerability in Adults with Epilepsy

Laurent M. Willems,
Milena van der Goten,
Felix von Podewils
et al.

Abstract: Background Antiseizure medication (ASM) as monotherapy or in combination is the treatment of choice for most patients with epilepsy. Therefore, knowledge about the typical adverse events (AEs) for ASMs and other coadministered drugs (CDs) is essential for practitioners and patients. Due to frequent polypharmacy, it is often difficult to clinically assess the AE profiles of ASMs and differentiate the influence of CDs. Objective This retrospective analysis aimed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 95 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Besides, differing assessment criteria and definitions may also play a role. Nevertheless, these results suggest tolerability issues of valproate treatment in SE patients, as shown recently in epilepsy patients [ 17 ].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Besides, differing assessment criteria and definitions may also play a role. Nevertheless, these results suggest tolerability issues of valproate treatment in SE patients, as shown recently in epilepsy patients [ 17 ].…”
Section: Discussionmentioning
confidence: 59%
“…To our best knowledge, this is the first study estimating the acute VIE incidence in SE patients. Like patients with epilepsy [ 17 ], valproate seems not so well tolerated in patients with SE. In this relatively small sample, VIE seems relatively frequent (10%), often occurred without hyperammonemia, and was possibly associated with preexisting liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of data from a large German multicenter study showed synaptic vesicle glycoprotein 2A modulators have a favorable adverse event profile, with BRV showing fewer psychobehavioral adverse events than LEV [ 28 ]. In EXPERIENCE, the incidences of psychiatric, cognitive, and behavioral TEAEs were similar in patients with psychiatric comorbidity who switched from LEV to BRV compared with patients who switched from other ASMs to BRV; this finding was also observed in patients without psychiatric comorbidity who switched from LEV to BRV compared with patients who switched from other ASMs to BRV.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the LAEP, HADS-D, and NDDI-E scores overlapped, a recent mediation analysis revealed that patient-reported depression and ASM-related adverse events jointly mediated the association between ASMs and QoL [ 37 ]. Adverse events must be carefully evaluated, and the adverse events profile should always be taken into consideration when selecting an ASM [ 38 ]. The number of ASMs was not significantly correlated with QoL.…”
Section: Discussionmentioning
confidence: 99%